Effect of starch as hydrocolloids for formation of a stable emulsion system in food - Lugovska, Oksana; Sidor, Vasyl; Kostova, Iliana (Lugovska, O. Effect of starch ashydrocolloids, the formation of a stable emulsion system in food / O. Lugovska, V. Sydor // Ukrainian food journal : internatinal scientific journal. – 2014. – Vol. 3. Issue 2. – P. 202–210., 2014)
The investigated properties of native starch in the emulsion show that their use in manufacturing processes may result in the blocking of heat exchangers (due to high peak viscosity), and the viscosity at the output of the production process with varying and unpredictable depends on the combination of temperature and mechanical stress. This makes the use in the production of modified starches, which pobut combines two types of modifications: stabilization and the stitching. Important is the number of active links per molecule of starch. Such starches are characterized by high resistance to the process conditions (temperature, homogenization, effects of acidic). In each case, selecting the optimal starch, should take into account the specific conditions of the process.
Keywords: в’язкість; нативний крохмаль; модифікований крохмаль; вязкость; нативный крахмал; модифицированный крахмал; viscosity; modified starch; native starch; кафедра експертизи харчових продуктів